The Influence Of Brand Awareness And Brand Image On Brand Loyalty (Study of Lion Air airline customers who have a Lion Air Passport Club in the Jakarta City area) - Widya Nengsih; Nandan Limakrisna; Anoesyirwan Moens (Greenation Research & Yayasan Global Resarch National, 2023)
The aim of this research is to determine and analyze: (1) Brand Awareness; (2) Brand Image; (3) Brand Loyalty and (3) The Influence of Brand Awareness and Brand Image on Brand Loyalty among Lion Air airline customers who have a Lion Air Passport Club in the City area. Jakarta, both simultaneously and partially. The research method used in this research is a descriptive survey and an explanatory survey, the unit of analysis in this research is Lion Air airline customers who have a Lion Air Passport Club in the Jakarta City area with a sample of 50 people. The type of investigation is causality, and the time horizon in this research is cross-sectional. Based on the research results, it was found that according to the brand awareness of Lion Air airline customers who have a Lion Air Passport Club in the Jakarta City area is generally relatively adequate, the Brand Image of Lion Air airline customers who have Lion Air The passport club in the Jakarta City area is appropriate and sufficient to meet the needs, brand loyalty of Lion Air airline customers who have a Lion Air Passport Club in the Jakarta City area is appropriate, as well as Brand Awareness and Brand Image (Brand Image) towards Brand Loyalty of Lion Air airline customers who have a Lion Air Passport Club in the Jakarta City area. However, partially Brand Awareness is more dominant in influencing Brand Loyalty than Brand Image. Because Brand Awareness influences Brand Loyalty, it is the first priority in improving employee performance. Therefore, Lion Air Group is advised to improve the quality of service in order to increase appropriate and good Brand Awareness, so that customers can feel satisfaction in using Lion Air Group airlines..